Synthesis of activated carbon from aguaje seeds (Mauritia flexuosa) for the adsorption of the N,N-dimethylamine - Beltrán-Suito, R.; Pinedo-Flores, A.; Bravo, F.; Ramos-Muñoz, J.; Picasso, G.; Sun-Kou, M.R. (Springer New York LLC, 2015)
Activated carbons (ACs) were prepared from aguaje seeds at different impregnation ratios of H.PO4/precursor equivalent to 0.5, 0.75, 1.0 and 1.5, for the adsorption of N,N-dimethylamine (DMA). The samples were characterized by N2-sorption (SBET), X-ray diffraction, infrared spectroscopy (FTIR), Boehm titration, scanning electron microscopy and energy-dispersive X-ray spectroscopy. The samples were successfully activated to obtain highly microporous surface (>95 %) with high total BET surface area (>695). Common acid functional groups were determined by the Boehm titration and FTIR. The kinetic data revealed that the results were better adjusted to pseudo-second order and Elovich models. To predict the adsorption process, different isotherm models were tested. The best fit isotherm model for AC-0.5 and AC-0.75 samples was the Temkin isotherm model. Meanwhile, the Langmuir isotherm was the best fit model for AC-1.0 and AC-1.5 samples. Moreover, it was found that the adsorption of DMA was highly influenced by the surface acidity and the microporosity of the carbons.
Keywords: Activated carbon; N,N-dimethylamine; Adsorption; Aguaje seeds; https://purl.org/pe-repo/ocde/ford#2.06.00